Vocal traits of hybrid fur seals: intermediate to their parental species - Page, B; Goldsworthy, SD; Mark Hindell (2001)
Vocal communication is important for species recognition in colonial breeding species such as fur seals, especially where closely related species that can hybridize breed sympatrically. This is the first study to describe the calls of hybrid fur seals. We investigated whether these vocalizations are intermediate to those of their parental species (Antarctic, Arctocephalus gazella, subantarctic, A. tropicalis, and New Zealand, A. forsteri) and discuss the evolutionary implications of hybrids having intermediate vocal traits. Hybrid males' bark calls were intermediate between two distinct groups formed by A. tropicalis and A. gazella/A. forsteri. Patterns of intermediate call characteristics were also discernible for pup attraction calls (given by females) but not for full threat calls (given by males), nor female attraction calls (given by pups); however, for all call types hybrid calls were distinct from those of their parental species. The pattern of hybrid calls being intermediate is consistent with the expectation that call traits are genetically inherited. Â© 2001 The Association for the Study of Animal Behaviour.